The Phenomenon Of Increasing Division During The Covid-19 Pandemic At Gorontalo Religious Court - Kamba, Sri Nanang Meiske (Universitas Negeri Gorontalo, 2022)
The rate of divorce cases during the COVID-19 pandemic at the Gorontalo Religious Court has increased significantly compared to talak cases submitted to husbands to their wives. The problems in this study are 1) What are the factors causing the increase in divorce during the Covid 19 pandemic? Moreover, 2) What are the legal consequences of increasing divorce cases during the COVID-19 pandemic at the Gorontalo Religious Court. The purpose of this study was to identify the causes of the increase in divorce lawsuits at the Gorontalo Religious Court during the Covid-19 pandemic. The type of approach used in this research is the legislation (Statute Approach) and the case approach (Cases Approach). Methods of collecting data using Library Research and analysis with legal interpretation. The results showed that the factors causing the increase in divorce cases during the COVID-19 pandemic in the Religious Courts were due to economic factors, continuous quarrels, third parties, and domestic violence. The issue of divorce in Law Number 1 of 1974 in principle adheres to the principle of complicated divorce as regulated in Article 39 paragraph 1. Furthermore, based on Article 114 of the Compilation of Islamic Law (